1988
DOI: 10.1080/0028825x.1988.10410112
|View full text |Cite
|
Sign up to set email alerts
|

The -3/2 law applied to some gorse communities, with consideration of line fitting

Abstract: A "self-thinning" line is fitted to size/ density data from gorse (Ulex europaeus L.) communities around Dunedin, New Zealand. Three methods of line fitting were triedwunweighted least squares, weighted least squares, and weighted least absolute deviations regressions; they yielded similar results. The slope of the fitted line depends on whether other species are included, and whether dead material is excluded. If both are done, the fitted slope is close to the theoretical-3/2 (-1.5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Gorse is known to follow the − 3/2 law of self-thinning ( Wilson & Lee 1988). A study of stand structure in gorse thickets of different ages showed that stem density declined from 32 to 6 stems m -2 over 15 years, when the stand was considered to be mature (Lee, Allen & Johnson 1986).…”
Section:    mentioning
confidence: 99%
“…Gorse is known to follow the − 3/2 law of self-thinning ( Wilson & Lee 1988). A study of stand structure in gorse thickets of different ages showed that stem density declined from 32 to 6 stems m -2 over 15 years, when the stand was considered to be mature (Lee, Allen & Johnson 1986).…”
Section:    mentioning
confidence: 99%
“…Historically, there are several regression methods used to estimate the two coefficients of the maximum size-density line, such as (1) arbitrarily hand fitting a line above an upper boundary of data points (Yoda et al 1963;Drew and Flewelling 1977), (2) fitting an ordinary least squares regression (OLS) or weighted least squares regression (WLS) through data points selected on a density-dependent mortality criterion (Ford 1975;Wilson and Lee 1988), and (3) estimating coefficients via major axis analysis or principal components analysis (PCA) based on chosen data (Mohler et al 1978;Hutchings and Budd 1981;Bi and Turvey 1997;Wilson et al 1999). The last two methods define an "average" maximum size-density line (Osawa and Sugita 1989) rather than a "biological" maximum size-density line (Smith and Woods 1997).…”
Section: Introductionmentioning
confidence: 99%
“…There are several statistical methods to estimate the two parameters of the self-thinning line, such as (1) placing a line by hand above an upper boundary of data points [ 3 , 7 ], (2) fitting least squares regressions[ 19 21 ], (3) estimating parameters through quantile regression [ 22 ], principal components analysis and reduced major axis regression (RMA) [ 23 , 24 ], and RMA method combined with jackknife estimation [ 25 ], (4) bisector regression approach [ 26 ], and (5) adopting stochastic frontier function to estimate the self-thinning line [ 27 , 28 ]. Zhang et al .…”
Section: Introductionmentioning
confidence: 99%